The gospel according to St John the Greek text with introduction and notes. - Westcott, Brooke Foss, 1825-1901 (Grand Rapids, MI Baker, 1880)
Includes bibliographical references and index.
Originally published in 1908 in two volumes; both volumes now in one.
Keywords: Bible. N.T. John -- commentaries